2016
DOI: 10.1016/j.jep.2016.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Cis- and Trans-gnetin H from Paeonia suffruticosa suppress inhibitor kappa B kinase phosphorylation in LPS-stimulated human THP-1 cells

Abstract: We demonstrated that cis- and trans-gnetin H suppress cytokine response in LPS-stimulated THP-1 cells by preventing activation of key signaling molecules, IKK-β, IκB α, and p65, involved in the NF-κB pathway and suggest the use of cis- and trans-gnetin H in potential therapies for conditions and diseases associated with chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Resveratrol was discovered as phytoalexin and has a variety of pharmacological activities, such as anti-pathogenic activities toward microorganisms (bacteria, fungi and viruses) and anti-tumor and anti-inflammatory activities. Some studies have suggested that some of these oligomers have significantly stronger antioxidant, antitumor and anti-inflammatory activities than their monomer resveratrol and that the mechanisms are also different; these properties have inspired scholars to look for new drug candidates with high selectivity and few side effects [10][11][12]. However, there is still no effective total synthesis method because of their structural complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Resveratrol was discovered as phytoalexin and has a variety of pharmacological activities, such as anti-pathogenic activities toward microorganisms (bacteria, fungi and viruses) and anti-tumor and anti-inflammatory activities. Some studies have suggested that some of these oligomers have significantly stronger antioxidant, antitumor and anti-inflammatory activities than their monomer resveratrol and that the mechanisms are also different; these properties have inspired scholars to look for new drug candidates with high selectivity and few side effects [10][11][12]. However, there is still no effective total synthesis method because of their structural complexity.…”
Section: Introductionmentioning
confidence: 99%
“…This was the first report on the large-scale extraction, enrichment and separation of oligostilbenes. The results of pharmacological studies revealed that SB, TV and TG had good antioxidant [5] , antibacterial [9] , anti-inflammatory [10] , [11] , anti-tumor [4] , [9] , [12] , cognitive function improvement [13] , hypoglycemic effects [4] , enzyme inventory activity [4] , etc. The SOP in this paper could produce high purity SB, TV and TG, and provided theoretical support for PSS as a new resource of oligostilbenes.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, SB, TV and TG had the highest content with important development and utilization value [3] , [7] , [8] . The bioactivities evaluation revealed that SB, TV and TG had good antioxidant [5] , antibacterial [9] , anti-inflammatory [10] , [11] , anti-tumor [4] , [9] , [12] , cognitive function improvement [13] , hypoglycemic effects [4] , enzyme inventory activity [4] , etc. As a kind of authorized edible oil, tree peony seed oil (TPSO) was widely concerned for its rich content of unsaturated fatty acids, which led to the increasing cultivation area of oil tree peony year by year [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have shown that activation of the NF-κB or JNK/P38 MAPK signaling pathway is an important way to induce high expression of IL8 . JAK-STAT3 is an upstream signaling molecule for NF-κB activation, which induces the expression of IL8. , P38/JNK MAPK, NF-κB, and JAK-STAT3 signaling pathways play vital roles in other inflammatory skin diseases, such as psoriasis and rosacea . One study reported that transgenic mice (K5.…”
Section: Discussionmentioning
confidence: 99%